Atomic-layer-deposited iron oxide on arrays of metal/carbon spheres and their application for electrocatalysis. (February 2016) - Xia, Xinhui; Wang, Yadong; Wang, Donghuang; Zhang, Yongqi; Fan, Zhanxi; Tu, Jiangping; Zhang, Hua; Fan, Hong Jin
Abstract: We construct high-performance oxygen reduction reaction (ORR) catalysts by a rational integration of metal tube (NiT), carbon spheres (CSs) and atomic-layer deposited Fe3 O4 . The preformed arrays of NiT/CSs are uniform coated by Fe3 O4 using atomic layer deposition (ALD) technique with variable thickness. The obtained NiT/CSs–Fe3 O4 hybrid nanoarrays have combined properties of inter-connected porous architecture (thus large surface area) and good mechanical robustness. The NiT/CSs–Fe3 O4 arrays exhibit enhanced electro-catalytic ORR properties with higher onset potential and catalytic current than other iron oxide-based counterparts, as well as noticeable methanol-tolerance and CO anti-poisoning due to the integrated architecture and probably a synergistic coupling effect. Our result verifies the useful application of ALD in fabrication of nanostructured electrocatalysts. The developed design protocol of active materials can be extended to other hybrid arrays for applications in electrochemical energy storage and sensing. Graphical abstract: Highlights: Rational designed nickel tube/carbon spheres-iron oxides ternary core/shell arrays. Atomic-layer-deposition used in fabrication of nanostructured electrocatalyst. Synergistic effect of the core–shell array leads to enhanced ORR property.